Neonatal melioidosis case report - lessons learned - Sylvia Daim; Ester Barnad; Victor Johnny; Maria Suleiman; Muhammad Jikal; Tock, Hing Chua; Christina Rundi (John Wiley & Sons Ltd, 2020)
In endemic regions, include melioidosis in the routine differential diagnosis of neonates with respiratory distress, and consider early empirical ceftazidime treatment for neonates with worsening respiratory distress